Financial crime in the EU : criminal records as effective tools or missed opportunities? - Stefanou, Constantin (Kluwer Law International The HagueNL, 2005)
Provides in-depth discussion on methodologies for collecting criminal records, the authorities maintaining such records, the contents of such records and who has access to them, as well as, conflicts with human rights and privacy legislation.